Structural investigations of epitaxial InN by x-ray photoelectron diffraction and x-ray diffraction - Hofstetter, Daniel; Despont, Laurent; Garnier, Michael Bernard Gunnar; Baumann, Esther; Giorgetta, Fabrizio R.; Aebi, Philipp; Kirste, Lutz; Lu, Hai; Schaff, William J. (My University, 2007)
The authors investigated a 1 µm thick molecular beam epitaxy–grown InN film by means of full hemispherical x-ray photoelectron diffraction and high resolution x-ray diffraction. While x-ray diffraction reveals that this nominally hexagonal InN layer contains roughly 1% of cubic phase InN, a comparison between measured and simulated x-ray photoelectron diffraction data allowed them to directly determine the polarity of the crystal. Furthermore, the data indicate that the InN surface consists of a mosaic of domains oriented at an azimuth of 180° to each other, where the azimuth corresponds to the rotation angle around the [0001] axis.